Predatory Short Selling and Market Volatility: an Empirical Analysis of The Impact of Leverage Constraints on The Stability of Financial Institutions on The Indonesia Stock Exchange - Najah, Neneng Putri; Hidayat, Agus Rohmat; Komarudin, Komarudin (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
This study analyzes the impact of predatory short selling on the stability of financial institutions on the Indonesia Stock Exchange by focusing on the role of leverage constraints in creating systemic vulnerability. Using panel data from 42 registered banks for the 2018-2023 period, this study applies an agent-based modeling approach combined with empirical analysis to understand the transmission mechanism of short selling to forced liquidation. The results show that financial institutions with a high leverage ratio (>8%) experience an increase in stock price volatility by 23.7% when facing intensive short selling pressure. The simulation model identifies three vulnerability regions: the safety region (leverage <6%), the vulnerability region (leverage 6%-8%), and the doomed region (leverage >8%). Empirical findings confirm that coordination between short sellers expands the doomed region, where liquidation becomes a single equilibrium. Panel regression analysis showed that every 1% increase in the short interest ratio increased the probability of forced liquidation by 0.47% in high-leverage institutions. The implementation of circuit breakers and short selling restrictions has proven effective in reducing manipulative short selling by 31% during the COVID-19 crisis period. This research provides an empirical justification for the temporary restriction of short selling on vulnerable financial institutions and contributes to the development of a more adaptive regulatory framework in emerging markets.